QUIZLET: APLIKASI PEMBELAJARAN BERBASIS SMARTPHONE ERA GENERASI MILENIAL - Dhany Efita Sari (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
Millennials are a generation that is familiar with the use of technology and the internet in everyday life. This generation can spend hours using internet technology through cellular phones or mobile phones that are more practical and easy to use. The process of education and learning in this generation certainly needs to apply some appropriate learning methods by using mobile phones based on smartphones so students are more interested and enthusiastic in participating in learning. Quizlet is a smartphone-based online learning device that can be used for all subjects and for all ages. Quizlet can be accessed by students through mobile phones based on Android or iOS. The purpose of this study is to explain the advantages of the Quizlet application that can be used in the millennial generation learning process. Literature studies are used to explain the advantages offered by the Quizlet application through the analysis of theory and literature that has been obtained.